Express Method of Analysis Morphological Parameters of Graphene Coatings on a Copper Substrate - V.S. Levitskiy; T.S. Koltsova; M.V. Kozlova; T.V. Larionova; V.O. Sobol (Журнал нано- та електронної фізики)
CVD method of a gas mixture of methane, hydrogen and argon was used for condensation of graphene layers on the copper substrate. Along with traditional methods of growth morphology studies, such as Raman spectroscopy and atomic force microscopy, the work for the rapid assessment of the degree of filling and the specific area of the graph area used the method multithreshold sections with a 3-dimensional representation of the image of the optical microscope, where the third Z-axis using the intensity scale. On the basis of the results obtained conclusions about the patterns of formation of graphene layers. Presence of the most likely areas of formation of graphene domains (~ 13 mm2) with a small time (10-20 minutes) of the production process. Increasing the process time of 30 minutes accompanied by increased uniformity of distribution space formed between the graphene domains to 200 mm2 high fractal dimension of the range of values HD 1,82 ... 2 0.